Предмет: Алгебра,
автор: Gitarist2777
Помогите пожалуйста
Приложения:
Ответы
Автор ответа:
0
3) (3-i)(2+i)+5i=6-2i+3i-(i)^2 +5i=6+i+1+5i=6i+7;
4)(5-3i)/(2-3i)=((5-3i)(2+3i)) / ((2-3i)(2+3i))=(10-6i+15i-9i^2) /(4-9i^2)=
=(19+9i)/13 i^2=-1
---------------
4)(5-3i)/(2-3i)=((5-3i)(2+3i)) / ((2-3i)(2+3i))=(10-6i+15i-9i^2) /(4-9i^2)=
=(19+9i)/13 i^2=-1
---------------
Похожие вопросы
Предмет: История,
автор: denisscerbyk123
Предмет: Українська мова,
автор: yasya3063
Предмет: История,
автор: oralbaevalejla40
Предмет: Литература,
автор: Арина260302